Identifying pedagogical and performance benefits of playing the euphonium and singing - Shaw, Edward James Jr. (Kansas State University, 2024)
This Master’s report focuses on a comparison of the physical and pedagogical benefits and challenges of comparing vocal pedagogy with euphonium pedagogy. The report will describe how this approach can be useful to an instrumental teacher and how they can implement the benefits in their own teaching. There are many ways that we can learn from a comparison of vocal and brass pedagogy. This report was written to answer the question, “Why is it important to use vocal pedagogy to strengthen our playing capabilities on wind instruments, specifically euphonium.” Using information already presented from some of the great pedagogical minds in both singing and wind playing, this report will begin by accounting for available resources to learn about these two pedagogical methods congruently. This chapter will include a review of important published books and articles relating to vocal and brass pedagogies. Next, this report will present applications and challenges I have personally learned and encountered from taking performance lessons in both singing and euphonium. Finally, the report will address how, as a teacher, one can implement vocal pedagogy elements into brass pedagogy and how in doing so, help students produce better tone, articulation, sound, and musicality.
Keywords: Euphonium; Singing; Low brass; Performance pedagogy